HANDBOOK ON FISH AGE DETERMINATION - a Mediterranean experience DIADROMOUS SPECIES - 6.1 Anguilla anguilla - Eleonora Ciccotti (FAO General Fisheries Commission for the Mediterranean (GFCM), 2019)
Fish age, among other biological parameters, is one of the most relevant pieces of data in reaching sustainable exploitation of fshery resources. Indeed, most analytical methods used in stock assessment require knowledge of demographic structure according to the age of stocks, as well as to recruitment, growth, maturity, natural mortality, etc., which are strictly linked to information on age and age structure. The literature on ageing analysis shows some gaps regarding ageing schemes, criteria and methodologies used in preparing calcifed structures. These aspects afect both the precision and accuracy of age estimation. One action that could be taken to overcome this gap was to formalize a handbook that clarifed approaches to ageing schemes, criteria and preparation methods. Having a common protocol is fundamental to decreasing relative/ absolute bias associated with the activities of age determination and to improving the precision (reproducibility and reduction of the coefcient of variation) of age readers from the various laboratories. In the light of these considerations, this handbook aims to be a guideline to standardizing the methods used in fsh ageing studies. The document is focused on a description of the general principles on which age analysis relies (assignment of birth date, preparation methods, aging scheme reading and identifcation of true and false rings). Moreover, common shared analysis methods can enable a high level of calibration among the diverse institutes involved, thus improving the quality and reliability of results. The volume is subdivided into fve main sections: small pelagic species, demersal species, cartilaginous species, large pelagic species and diadromous species. For each section, information on extraction and storage, preparation method, interpretation of age (age scheme) and ageing criteria are provided by species. In total, 30 species were analysed: 6 small pelagic, 12 demersal, 5 cartilaginous, 6 large pelagic and the European eel. These species represent some of the most ...